Effective Management of Neuromuscular Blockade in Obese Patients Undergoing Abdominal Surgery: A Comparative Study - Kanteti, Krishna Priya (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Overweight adults are 4 times more likely to experience these problems; therefore, restoring normal lung function requires the complete removal of any remaining neuromuscular blockade (NMB) and maintenance of muscle relaxation. This study aimed to identify an effective procedure for NMB in obese patients undergoing abdominal surgery. Materials and Methods: Our study included 34 participants ranging in age from 18 to 56 years, with a mean age of 36.8 ± 2.7 years. The study population comprised of 15 men (45%) and 19 women (55%). Participants were divided into two groups: The control group consisted of 21 individuals with a normal body mass index (BMI), whereas the experimental group consisted of 13 individuals with a BMI that varied between 30.1 and 40.0. Results: Patients in the control group, who responded to T2 and T3 stimulation in the in the four-stimulation mode, received sugammadex (2 mg/kg), totaling 205.90 ± 11.14 mg. The experimental group did not receive any medications to facilitate recovery from NMB. Patients in control group had a quicker recovery time for NMB, averaging 48.00 ± 12.82 minutes, compared to Group 2, which averaged 64.91 ± 4.68 min (t = −4.636; P < 0.0001). Conclusions: After surgery in obese individuals, it is essential to rapidly and absolute revival of NMB and perform neuromuscular monitoring to evaluate the efficacy of removing the muscle relaxant and ensuring that no residual NMB remains.